Pedagogical Leadership for Identifying Teacher Needs in Learning Partnerships: A Systematic Literature Review - Widyawati, Ellya Agustin; Widiyan, Agung Purwa (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Pedagogical leadership plays a critical role in fostering teacher professional learning by ensuring that teachers’ needs are accurately identified to support collaborative and responsive learning environments. However, evidence regarding how pedagogical leadership facilitates the identification of teacher needs within learning partnerships remains fragmented across the literature. This study aims to synthesize current evidence on pedagogical leadership practices for identifying teacher needs in learning partnerships through a Systematic Literature Review (SLR). The review analyzed 18 peer-reviewed studies published between 2021 and 2025, retrieved from Google Scholar using the Publish or Perish application. The selected studies were examined through a systematic process of screening, data extraction, and thematic synthesis. The findings indicate that pedagogical leadership extends beyond administrative responsibilities by integrating instructional supervision, classroom observation, collaborative professional learning communities, and participatory dialogue with teachers and educational stakeholders to identify teachers’ professional learning needs. Effective leadership practices also encourage teacher engagement in continuous professional development, collaborative learning, and technology-responsive instructional improvement. The review further identifies persistent challenges, including limited financial resources, variations in teachers’ professional readiness, insufficient digital competence, and uneven institutional support for sustainable learning partnerships. The synthesis highlights that identifying teacher needs constitutes a strategic pedagogical process that strengthens professional learning, promotes collaborative educational ecosystems, and enhances instructional quality in elementary schools. These findings underscore the importance of repositioning school leadership from a managerial orientation toward pedagogical leadership that supports technology-responsive teacher development and sustainable learning partnerships.